Evaluation of the EX-O3 Dialyser Cartridge. Issue 5795 (29th January 1972) - Burton, J. A.; Lindsay, R. M.; Kennedy, A. C.
Abstract : Fifty-five dialyses were performed using the EX-O3 dialyser cartridge. The performance of the dialyser in respect of urea, creatinine, phosphate, and uric acid dialysance is comparable to that of the Travenol Ultra-Flo 100 (cuprophane). It is rather more compact, is easy to operate, has minimal blood loss, and a low priming volume. Ultrafiltration was quite adequate and the dialyses were uncomplicated by side effects. A failure rate of 7% occurred but none of the patients lost any appreciable quantity of blood.